The Development of Digital Design Method in Ikat Weaving’s Motif - Endri Sintiana Murni; Refanda Wahyu Hadiantoro; Mulyanto Mulyanto (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2023)
Ikat weaving is one of the Indonesian traditional textile arts commonly found in various parts of the country. Each region typically has its own motifs, designed manually and spontaneously without predesign stages. Therefore, developing a method to design weaving motifs is necessary to avoid spontaneous, monotonous products. This work attempted to explore the most efficient method in the ikat weaving design process, which would be helpful for Indonesian ikat weaving industries to deliver more diverse ikat weaving designs. To this end, we conducted a study in one of the ikat weaving workshops in Sukoharjo Regency, Indonesia. This participatory action research and development produced Adaptive ikat weaving templates that could be used to create various designs with different sizes. The template was designed entirely digitally using Firealpaca. The color application was also performed. The development of the digital ikat weaving design method is expected to encourage ikat weaving industries to present fresher, appealing motifs.Ikat weaving is one of the Indonesian traditional textile arts commonly found in various parts of the country. Each region typically has its own motifs, designed manually and spontaneously without predesign stages. Therefore, developing a method to design weaving motifs is necessary to avoid spontaneous, monotonous products. This work attempted to explore the most efficient method in the ikat weaving design process, which would be helpful for Indonesian ikat weaving industries to deliver more diverse ikat weaving designs. To this end, we conducted a study in one of the ikat weaving workshops in Sukoharjo Regency, Indonesia. This participatory action research and development produced Adaptive ikat weaving templates that could be used to create various designs with different sizes. The template was designed entirely digitally using Firealpaca. The color application was also performed. The development of the digital ikat weaving design method is expected to encourage ikat weaving industries to present fresher, appealing motifs.